(untitled) (Research, Society and Development, 2019)
The present study aims to analyze basic education in the small town of Cruzeta/ RN. The methodology used is qualitative, consisting of a case study with members of the team that form the Education and also civil society of the small town. Data were collected through a questionnaire made available through a social network, containing four subjective questions about basic education. Among the results found, it is evident by the subjects that education is a priority for the success of a society and that it is fundamental for the transformation and development of the human being as a social being, thus creating a basis for knowledge and a critical view on the reality. At the end of the study it is evidenced that the basic education of the municipality of Cruzeta is considered good and has been recognized at the state and even national levels, with emphasis on the care of the physical structure and the staff, as well as the participation of students in prizes, but some improvements are necessary, highlighting the continued qualification for the teachers of the small town.